2019
DOI: 10.3759/tropics.ms19-04
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thinning on anatomical characteristics and wood properties of 12-year-old <i>Eucalyptus camaldulensis</i> trees planted in Thailand

Abstract: To clarify the effects of thinning on the growth and wood quality of Eucalyptus camaldulensis trees grown in Thailand, the growth characteristics, anatomical characteristics, and wood properties of T5 clones, which are used on plantations to produce pulpwood, were investigated. Core samples were collected from trees grown on both thinned and unthinned (i.e., control) plots. The effects of thinning on the trees anatomical characteristics and wood properties were evaluated at bark side (2 cm from the bark) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…This also occurred in Acacia salicina, where the treatment had a decrease in specific gravity value by 3.8% (Hegazy et al, 2014). However, a different result was reported in a 12-years-old Eucalyptus camaldulensis plantation, where the BD value was increased by 5.7%, without the alteration of the compressive strength parallel to grain (under green conditions; Aiso-Sanada et al, 2019). In Calabrian pine (Pinus nigra Arnold subsp.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…This also occurred in Acacia salicina, where the treatment had a decrease in specific gravity value by 3.8% (Hegazy et al, 2014). However, a different result was reported in a 12-years-old Eucalyptus camaldulensis plantation, where the BD value was increased by 5.7%, without the alteration of the compressive strength parallel to grain (under green conditions; Aiso-Sanada et al, 2019). In Calabrian pine (Pinus nigra Arnold subsp.…”
Section: Introductionmentioning
confidence: 87%
“…Larix kaempferi (Kim et al, 2016), Eucalyptus grandis hybrid (Filho et al, 2018), Eucalyptus camaldulensis (Aiso-Sanada et al, 2019), and Pinus koraiensis (Seo et al, 2019). In teak, previous studies reported that thinning and pruning treatments significantly increase the radial growth of the remaining stands (Budiadi et al, 2017;Kanninen et al, 2004;Víquez and Pérez, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…A dense mat of surface roots can extend 20 m laterally in mature trees, and taproots can extend to depths of at least 10 m to access groundwater (Bacon et al., 1993). E. camaldulensis growth and size have been linked to water availability and competition (Aiso‐Sanada et al., 2019; Horner et al., 2009). Large E. camaldulensis trees inhibit the growth rates of smaller trees within a zone up to 16 times as wide as their diameter at breast height (DBH) (Opie, 1968).…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, eucalyptus plants are widely planted all over the world and many researchers have extensively studied eucalyptus cultivation widely [1][2][3][4][5][6]. Eucalyptus is cheap, easy to grow and has many uses, such as being extracted as a mosquito and insect repellent, the essential oils are used to relieve nasal congestion and the bark is finely ground used to make incense.…”
Section: Introductionmentioning
confidence: 99%